A study on the teaching of non-Chinese students in Malaysia primary schools - Keat Yeap, Chun; Shi Ng, Lay (Opción, 2019)
Considering Malaysia with Chinese language education for both Chinese and non-Chinese students in Chinese primary schools, the academic performance of non-Chinese students is not as good as those Chinese students. Therefore, the present study investigated this issue from the perspective of teachers. Through questionnaires and face-to-face interviews, this research has looked into the teaching of non-Chinese students. The findings show that teachers are giving a “poor” performance evaluation to non-Chinese students in terms of their learning patterns, learning attitude, learning methods, and learning outcomes.